Circulating Spexin levels in pregnant women with and without gestational diabetes - Simsir, Coskun; Kalem, Muberra Namli; Kalem, Ziya; Var, Turgut; Bakirarar, Batuhan; Coskun, Bugra; Coskun, Bora (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Several previous studies suggest that SPX plays a role in appetite control and body weight and blood glucose regulation. The aim of this study to determine SPX levels in healthy pregnancies and in gestational diabetes (GDM) and to investigate the association of SPX levels with weight gain and lipid and glucose metabolism in subjects with and without GDM. Methods: A total of 44 women with GDM and 44 women without GDM were randomly enrolled who applied for GDM screening during the 24-28th week of pregnancy. Demographics, blood glucose and lipid profiles and Spexin levels were compared between groups. Results: The mean age, BMI, and weight gain during pregnancy were higher in the GDM group. The LDL cholesterol, Hba1c, SPX and glucose levels in response to OGTT were higher in the GDM group. The SPX levels were correlated with Hba1c and blood glucose levels after OGTT, and were not correlated with the age, BMI, weight gain during pregnancy, lipid parameters, and fasting blood glucose levels in the whole study population. Conclusions: SPX levels were higher in the GDM group compared with non-GDM group and SPX levels were correlated with HbA1c levels and post-OGTT glucose levels but not with fasting glucose levels.